DETERMINATION OF ANTIMICROBIAL ACTIVITY OF INFUSION FROM ABOVEGROUND PART OF LOPHANTHUS ANISATUS(Benth). (Conferencea, 2022)
The purpose of this work was to determine the antimicrobial activity of the infusion from the aboveground part of Lophanthus anisatus (bens). Studies have shown that the growth inhibition zone of Candida albicans is 28 mm, E.coli – 22 mm, Bacillus subtilis – 10 mm, St. Epidermidis – 10 mm, St. Aureus – 7 mm. The results obtained showed that the studied infusion from the aboveground part of lophanthus anisatus has pronounced antimicrobial activity against Candida albicans and moderate antibacterial activity against some gram-negative enterobacteria and conditionally pathogenic microorganisms.